Teachers' Perceptions of Students' Traditional and Nontraditional Career Choices - Tomini, Brenda A.; Page, Stewart (Canadian Journal of Counselling and Psychotherapy, 2007)
The present study examined perceptions toward student career choices, of 197 Canadian teachers (61 males and 136 females) enrolled in the teachers' In-Service Program at the Faculty of Education, University of Windsor. Each teacher examined one of eight written vignettes describing a student currently making a career decision. In a factorial design, three factors, student gender, type of occupational choice, and traditionality of the student's extracurricular activities, differed systematically across the eight vignettes. In responses to Likert (7-point) rating scales, both male and female teachers were more likely to encourage the traditional rather than nontraditional male student, and the nontraditional rather than the traditional female student. Traditionalitv of student activities did not significantly affect judgments regarding careers of males versus females.